Artificial intelligence-assisted phase recognition and skill assessment in laparoscopic surgery: a systematic review - Liao, Wenqiang; Zhu, Ying; Zhang, Hanwei; Wang, Dan; Zhang, Lijun; Chen, Tianxiang; Zhou, Ru; Ye, Zi (Frontiers in Surgery, 2025)
With the widespread adoption of minimally invasive surgery, laparoscopic surgery has been an essential component of modern surgical procedures. As key technologies, laparoscopic phase recognition and skill evaluation aim to identify different stages of the surgical process and assess surgeons’ operational skills using automated methods. This, in turn, can improve the quality of surgery and the skill of surgeons. This review summarizes the progress of research in laparoscopic surgery, phase recognition, and skill evaluation. At first, the importance of laparoscopic surgery is introduced, clarifying the relationship between phase recognition, skill evaluation, and other surgical tasks. The publicly available surgical datasets for laparoscopic phase recognition tasks are then detailed. The review highlights the research methods that have exhibited superior performance in these public datasets and identifies common characteristics of these high-performing methods. Based on the insights obtained, the commonly used phase recognition research and surgical skill evaluation methods and models in this field are summarized. In addition, this study briefly outlines the standards and methods for evaluating laparoscopic surgical skills. Finally, an analysis of the difficulties researchers face and potential future development directions is presented. Moreover, this paper aims to provide valuable references for researchers, promoting further advancements in this domain.